Nursing staff connect libraries with improving patient care but not with achieving organisational objectives: a grounded theory approach. (March 2014) - Chamberlain, David
Abstract Background Health organisations are often driven by specific targets defined by mission statements, aims and objectives to improve patient care. Health libraries need to demonstrate that they contribute to organisational objectives, but it is not clear how nurses view that contribution. Objectives To investigate ward nursing staff motivations, their awareness of ward and organisational objectives; and their attitudes towards the contribution of health library services to improving patient care. Method Qualitative research using focus group data was combined with content analysis of literature evidence and library statistics (quantitative data). Data were analysed using thematic coding, divided into five group themes: understanding of Trust, Ward and Personal objectives, use of Library, use of other information sources, quality and Issues. Four basic social‐psychological processes were then developed. Results Behaviour indicates low awareness of organisational objectives despite patient‐centric motivation. High awareness of library services is shown with some connection made by ward staff between improved knowledge and improved patient care. Conclusion There was a two‐tiered understanding of ward objectives and library services, based on level of seniority. However, evidence‐based culture needs to be intrinsic in the organisation before all staff benefit. Libraries can actively engage in this at ward and board level and improve patient care by supporting organisational objectives.